Odpowiedzi

2009-11-17T15:06:45+01:00
A)x+2y=-2
2x-y=1

3x+y=-1

d)
2x+y=9
2x-y=1

4x=10

g)2x+3y=4
8x-5y=-1
10x-2y=3
Najlepsza Odpowiedź!
2009-11-17T16:49:01+01:00
A)
{x-2=-2
2x-y=1
x=-2+2
2x-y=1
x=0
2*0-y=1
x=0
-y=1|:(-1)
x=0
y=-1
b)
{x+4y=-2
3x-8y=10
x=-2-4y
3*(-2-4y)-8y=10
x=-2-4y
-6-12y-8y=10
x=-2-4y
-20y=16|:(-20)
x=-2-4y
y=-4/5
x=-2-4(-4/5)
y=-4/5
x=-2+1/5
y=-4/5
x=-1i4/5
y=-4/5
c){x-2y=3
-2x+y=0
x=3+2y
-2(3+2y)+y=0
x=3+2y
-6-4y+y=0
x=3+2y
-3y=6|:(-3)
x=3+2y
y=-2
x=3+2(-2)
y=-2
x=-1
y=-2
d){2x+y=9
5x-4y=3
y=9-2x
5x-4(9-2x)=3
y=9-2x
5x-36+8x=3
y=9-2x
13x=39|:13
y=9-2x
x=3
y=9-2*3
x=3
y=9-6
x=3
y=3
e)
{3x-2y=5
2x-y=4
3x-2y=5
-y=4-2x|:(-1)
3x-2y=5
y=-4+2x
3x-2(-4+2x)=5
y=-4+2x
3x+8-4x=5
y=-4+2x
-x=-3|:(-1)
y=-4+2x
x=3
y=-4+2*3
x=3
y=-4+6
x=3
y=2
f)
2x+9y=-9
-3x+3y=8
2x+9y=-9
3y=8+3x|:3
2x+9y=-9
y=8+3x/3(przez 3)
2x+9*8+3x/3=-9 trzeba skrocic9i3
y=8=3x/3
2x+24+9x=-9
y=8+3x/3
11x=-9-24
y=8+3x/3
11x=-33|:11
y=8+3x/3
x=-3
y=8+3*(-3)/3
x=-3
y=8-9/3
x=-3
y=-1/3
g)
{2x+3y=4
8x-5y=-1
2x=4-3y|:2
8x-5y=-1
x=4-3y/2
8*4-3y/2-5y=-1trzeba skrocic8i2
x=4-3y/2
16-12y-5y=-1
x=4-3y/2
-17y=-1-16
x=4-3y/2
-17y=-17|:(-17)
x=4-3y/2
y=1
x=4-3*1/2
y=1
x=4-3/2
y=1
x=1/2
y=1
h)
{x-y=0
x+y+z=4
x+2y+3z=9
x=y
y+y+z=4
y+2y+3z=9
x=y
2y+z=4
3y+3z=9
x=y
z=4-2y
3y+3(4-2y)=9
x=yz=4-2y
3y+12-6y=9
x=y
z=4-2y
-3y=-3|:(-3)
x=y
z=4-2y
y=1
x=1
z=4-2*1
y=1
x=1
z=2
y=1